2004
DOI: 10.1152/ajplung.00184.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of heat shock factor 1 in inhibition of NF-κB pathway during heat shock response-mediated lung protection

Abstract: Wirth, Delphine, Fabrice Bureau, Dorothée Melotte, Elisabeth Christians, and Pascal Gustin. Evidence for a role of heat shock factor 1 in inhibition of NF-B pathway during heat shock responsemediated lung protection. Am J Physiol Lung Cell Mol Physiol 287: L953-L961, 2004. First published June 25, 2004 doi:10.1152/ ajplung.00184.2003.-Heat shock transcription factor (HSF)-1 is recognized as a central component of the heat shock response, which protects against various harmful conditions. However, the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…More interestingly, p50 homodimers are translocated into nuclei and activated in Hsp27-overexpressing MCF-7/adr cells that are known to repress NF-B activity. Various models have shown that HSF-1 and NF-B mutually repress (63,64). Thus, the absence of HSF-1 activity led to activation of mutant p53 and NF-B, which in turn can bind in the MDR1 promoter and transcribe P-gp in MCF-7/adr cells.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, p50 homodimers are translocated into nuclei and activated in Hsp27-overexpressing MCF-7/adr cells that are known to repress NF-B activity. Various models have shown that HSF-1 and NF-B mutually repress (63,64). Thus, the absence of HSF-1 activity led to activation of mutant p53 and NF-B, which in turn can bind in the MDR1 promoter and transcribe P-gp in MCF-7/adr cells.…”
Section: Discussionmentioning
confidence: 99%
“…6,61 Under these conditions, heat shock proteins were implicated in NF-B inhibition. 62 In contrast, we used 40°C heat exposure for 60 minutes, thereby mimicking short-term fever spikes that are commonly observed in patients with systemic infections. Previously, we found no evidence that under these conditions neutrophils up-regulated expression of heat shock proteins, even when assayed up to 4 hours (eg, HSP70 and HSP90).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hsf1 is required for normal development of the placenta, and female Hsf1 −/− mice are infertile (Xiao et al 1999;Christians et al 2000). Hsf1 −/− mice are more susceptible to lipopolysaccharide-induced mortality, cadmium-induced pulmonary damage, and hydrochloric acid-or ethanol-induced gastric lesions (Xiao et al 1999;Wirth et al 2004;Tanaka et al 2007). In the auditory system, Hsf1 −/− mice demonstrate increased susceptibility to noise trauma (Sugahara et al 2003;Fairfield et al 2005).…”
Section: Figmentioning
confidence: 99%